Information technology governance: an analysis of the approach in Ecuador - Andrés Gavilanes- Molina; Vicente Merchán- Rodríguez (Bulletin of Electrical Engineering and Informatics, 2022)
This work aims to show the Ecuadorian IT governance reality using descriptive research to analyze the approach of IT decisions. Indeed, one hundred and one private and governmental organizations were surveyed to examine their IT governance approach through a decision-making matrix model of responsibilities. The purpose is to distinguish IT governance perspectives and archetypes for IT decision-making, so that we collect relevant information about decision-making of executives, IT executives, C-level, and business unit leader business in a developing economy context. The survey results are conclusive; business monarchy is the centralized approach for decision-making in Ecuador. For instance, IT governance in Ecuador is different from other Latin American nations in terms of digital culture, maturity, and effectiveness. On the other hand, this work encourages practitioners and scholars to increase the research scope to create, adopt, or adapt IT governance decision-making models for low-income countries. This is another step on the ongoing discussion in the extant IT governance literature, rather than as a ﬁnal answer. Finally, future work will analyze and contrast the past normality with the post-pandemic period in Ecuador. Hence, using a survey on Ecuadorian IT governance structures, practices and behaviors will show the IT governance changes, perceptions, and trends.